PENGARUH KEPEMIMPINAN, IKLIM ORGANISASI DAN MOTIVASI BERPRESTASI TERHADAP KINERJA KARYAWAN PT. BINTANG MANDIRI FINANCE JAWA BARAT - Rosmita Rosmita; Kaman Nainggolan (LPPM Universitas BSI, 2015)
Abstract - This study aims to analyze the contribution of Leadership Behavior, Organizational Environment and Achievement Motivation on Employee Performance. The study was conducted at PT Mandiri Star Finance (Limited) branch office in West Java, with a population of 186 people. Researchers selected 128 sampe by using random sampling method. The research found out that there is a positive effect of the contribution of leadership behavior, and achievement motivation on employee performance, while the organizational climate has a negative effect on the performance of employees, and therefore was excluded from the model.The leadership behavior and achievement motivation are important factors that must be improved to increase employee performanceKeywords: Behavioral Leadership, Achievement Motivation, Employee Performance